2006
DOI: 10.1188/06.onf.603-610
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Assessment of Fatigue and Health Status in Greek Patients With Breast Cancer Undergoing Adjuvant Radiotherapy

Abstract: Findings contribute to the growing body of evidence regarding fatigue and its impact on health status in Greek patients with breast cancer and provide insights for effective nursing assessment, patient education, and symptom management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
18

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 27 publications
(53 reference statements)
4
22
0
18
Order By: Relevance
“…In this longitudinal survey demographic variables and factors associated with the tumour and anti-cancer treatment were unrelated to the fatigue. A large body of evidence exists to support the finding that CRF during anti-cancer treatment is not associated with tumour stage (12,22,23,46,51,56,60,(68)(69)(70) or any demographic (12,22,23,34,49,55,56,60,62,64,(66)(67)(68)(69)(70)(71) or treatment-related variables (12,22,23,46,51,53,55,60,64,(68)(69)(70)(71)(72). In contrast, two studies have reported that females experience more fatigue then males (62,73), three have demonstrated an association between increasing age and lower fatigue (12,34,53), one between marital status and fatigue, with divorced women experiencing the most fatigue …”
Section: Fatigue During Anti-cancer Treatmentmentioning
confidence: 79%
“…In this longitudinal survey demographic variables and factors associated with the tumour and anti-cancer treatment were unrelated to the fatigue. A large body of evidence exists to support the finding that CRF during anti-cancer treatment is not associated with tumour stage (12,22,23,46,51,56,60,(68)(69)(70) or any demographic (12,22,23,34,49,55,56,60,62,64,(66)(67)(68)(69)(70)(71) or treatment-related variables (12,22,23,46,51,53,55,60,64,(68)(69)(70)(71)(72). In contrast, two studies have reported that females experience more fatigue then males (62,73), three have demonstrated an association between increasing age and lower fatigue (12,34,53), one between marital status and fatigue, with divorced women experiencing the most fatigue …”
Section: Fatigue During Anti-cancer Treatmentmentioning
confidence: 79%
“…The most frequent primary tumor sites were breast and colorectal. 11.0 (9.1); 9.0 (0-53) 8.6 (7.6); 6.13 (0-34) 10 …”
Section: Discussionmentioning
confidence: 98%
“…It has been validated in French [5], Dutch [4], Swedish [15], Greek [10], and Chinese [18] languages. The PFS-R was evaluated psychometrically in a cross-sectional study of women with breast cancer [16] following the development of the original PFS [17].…”
Section: Introductionmentioning
confidence: 99%
“…Outros estudos sobre o tema têm adotado o mesmo ponto de corte, o que facilita comparações (4,(15)(16)(17)(18).…”
Section: Discussionunclassified
“…Durante a radioterapia, apenas 13% das pacientes referiram fadiga (15) e, em pacientes que realizaram terapia hormonal (4) o resultado foi semelhante (15,2%). Em pacientes antes do início de quimioterapia adjuvante, a prevalência de fadiga foi de 28% (16), mas em pacientes livres do câncer de mama, fadiga esteve presente em 41% (17) e 66,1% das amostras (18).…”
Section: Discussionunclassified